The The Influence of using MALL on EFL Students’ Language Learning - Moh Rafli Wahyudi; Made Hery Santosa; Luh Indrayani (Universitas Pendidikan Ganesha, 2025)
The suboptimal utilization of mobile technology in English as a Foreign Language (EFL) instruction highlights the need for more interactive, flexible, and learner-centered approaches. The integration of Mobile-Assisted Language Learning (MALL) has been recognized for its potential to enhance students’ proficiency, motivation, and engagement. Therefore, this study aims to explore the effectiveness of MALL implementation in EFL learning contexts by reviewing ten empirical articles published between 2019 and 2024, using a systematic review approach based on the PRISMA protocol. A total of 1,000 publications were identified through Google Scholar using the keywords “MALL,” “Mobile Assisted Language Learning,” “EFL,” and “Mobile platform.” After applying screening criteria, ten open-access studies were selected for analysis. The findings indicate that MALL significantly supports vocabulary acquisition, listening, speaking, and grammar skills through high accessibility, real-time feedback, and interactive features that promote learner autonomy. Furthermore, the integration of messaging platforms strengthens the collaborative and communicative dimensions among learners, creating a more dynamic and participatory learning environment. In conclusion, MALL holds promise as a transformative approach to EFL education that is both flexible and learner-centered.